Reproductive Health Practice of Married Women in the Rural Community of Dhamrai Upazila, Dhaka (Anwer Khan Modern Medical College Journal, 2013)
Reproductive health is an emerging issue in Bangladesh as well as in the world. Women reproductive health is relatively a new area of health intervention in Bangladesh and recently it is an important issue. Among the women, married adolescents are particularly vulnerable regarding reproductive health problem in Bangladesh. This descriptive cross sectional study was carried among 534 married women of reproductive age by purposive sampling from 22nd to 28th December, 2012 in different villages of Dhamrai Upazila, Dhaka. Data were collected on a pretested questionnaire by face to face interview. Data were analyzed manually and by using computer. The study revealed that majority of the women had either primary (33%) or secondary level (39%) education with mean age of 29±7.33 years. Most of them (86%) were house-wives and dependant on their husband for financial support and major segment (52%) had poor monthly income (TK